Administrative responsibility and ethics - Woode, Samuel N
The article discusses the importance of administrative responsibility and ethics in public administration. The public servants, in the discharge of their duties encounter conflicting responsibilities and obligations to diverse interests. Some of these interests are: (1) the state and government. It argues that a public servant should be loyal to the government of the day (2) responsibility to political superiors. The public servant should try to achieve an integration of different interests into something of a general interest in public policy-making. A public servant representing the specific-techinical-fact and has to submit to the minister representing the general-political-value end of the policy-mak
Keywords: Ethics; Administrative Responsibility